Borobudur Temple and The Sacred Heart Shrine: Studying The Buddhism and The Catholic Pilgrimage Sites in South Java - Tuhri, Mufdil (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This article examines pilgrimage sites in Indonesia's religious traditions that play an important role in emphasizing the inclusive dimension of Indonesian people in general. This study examines the dimensions of religious pilgrimages in the religious traditions of the dominant religions in Indonesia, namely Buddhism and Catholicism. The research was carried out in the context of Central Java, namely Borobudur Temple as a Buddhist site and the Temple of the Sacred Heart as a Catholic site. This study reveals several aspects of the similarities and differences in the dimensions of pilgrimage sites according to both traditions. In conclusion, this article shows that Indonesian society is a society that is open and accepts the presence of religious sites in public spaces and accepts the functions of these religious sites as part of tourism.Artikel ini membahas situs ziarah dalam tradisi keagamaan di Indonesia yang berperan penting dalam menekankan dimensi inklusif masyarakat Indonesia pada umumnya. Kajian ini mengkaji dimensi ziarah agama dalam tradisi keagamaan agama dominan di Indonesia, yaitu Budha dan Katolik. Penelitian ini dilakukan dalam konteks Jawa Tengah yaitu Candi Borobudur sebagai situs Budha dan Candi Hati Kudus sebagai situs Katolik. Penelitian ini mengungkap beberapa aspek persamaan dan perbedaan dimensi situs ziarah menurut kedua tradisi tersebut. Kesimpulan dari artikel ini adalah bahwa masyarakat Indonesia adalah masyarakat yang terbuka dan menerima keberadaan situs religi di ruang publik serta menerima fungsi situs religi tersebut sebagai bagian dari pariwisata.